Estudo químico e farmacológico das cascas do tronco de Calophyllum brasiliense (Clusiaceae) - Rea, Alexandre [UNIFESP] (2013)
In the present work, was conducted the chemical study of methanol extract from the stem barks of Calophyllum brasiliense (Clusiaceae). This extract was also evaluated for antiparasitic potential and displayed high antitripanossomal potential. Therefore, this extract was subjected to partition with EtOAc and the obtained organic phase was subjected to evaluation of antiparasitic potential, showing excellent antitripanossomal activity (IC50 = 22 g/mL) while the same phase was inactive when evaluated against Leishmania sp.. Thus, this material was submitted to chromatographic procedures such as column chromatography (normal phase silica gel and Sephadex LH-20) affording the isolation of coumarin 6-hydroxy-4-propyl-5(3-hydroxy-2-methyl-1-oxobutyl)-6”,6” dimethylpyran-[2”,3”:8,7]-benzopyran-2-one, known as soulamarin, and the first occurrence of this compound C. brasiliense. The structure of this substance was defined by spectroscopic and spectrometric methods such as mass spectrometry (MS) and nuclear magnetic resonance (NMR), including twodimensional experiments. Finally, the coumarin soulamarin has been tested against trypomastigotes forms of T. cruzi and showed IC50 value of 85.3 g/mL, similar than determined to positive control benznidazol (IC50 of 114.6 g/mL). However, this value is higher than that found for the EtOAc partition phase of MeOH crude extract, suggesting that may be present in this material other inactive compounds that can act synergistically when in mixture with coumarin soulamarin.